STUDI LITERATUR: ANALISIS PENGARUH DOPING PADA KATODA NMC 811 DALAM MENINGKATKAN KINERJA ELEKTROKIMIA BATERAI LITHIUM-ION - Ambarwati, Vita; Masyrofi, Mohammad Iqbal Faza (JURNAL DARMA AGUNG, 2024)
Lithium-ion batteries (LIBs) are a widely used energy storage technology, especially in electric vehicles and renewable energy, due to their high energy density and long cycle life. One of the promising cathode materials is NMC 811 (Nickel Manganese Cobalt) due to its large energy capacity. However, the issues of capacity degradation and cycle stability are still major challenges in the development of this material. This research focuses on doping strategies to improve the electrochemical performance of NMC 811 cathode. The addition of elements such as aluminum (Al), tin (Sn), and scandium (Sc) has been shown to be effective in improving retention capacity, conductivity, and structural stability. The purpose of this study is to analyze the effect of doping on the specific capacity, coulombic efficiency, cycle stability, and ionic conductivity of NMC 811 cathodes, while identifying the most effective dopant elements. This research uses a descriptive qualitative approach with literature study techniques from various scientific sources. The results show that doping is an effective solution to overcome the limitations of NMC 811 cathode, supporting the development of better lithium-ion batteries for the future. In addition to improving electrochemical performance, doping also contributes to a more efficient and sustainable energy storage technology.